Antimicrobial resistance and management of invasive Salmonella disease. (19th June 2015) - Kariuki, Samuel; Gordon, Melita A.; Feasey, Nicholas; Parry, Christopher M.
Abstract: Invasive Salmonella infections (typhoidal and non-typhoidal) cause a huge burden of illness estimated at nearly 3.4 million cases and over 600, 000 deaths annually especially in resource-limited settings. Invasive non-typhoidal Salmonella (iNTS) infections are particularly important in immunosuppressed populations especially in sub-Saharan Africa, causing a mortality of 20–30% in vulnerable children below 5 years of age. In these settings, where routine surveillance for antimicrobial resistance is rare or non-existent, reports of 50–75% multidrug resistance (MDR) in NTS are common, including strains of NTS also resistant to flouroquinolones and 3rd generation cephalosporins. Typhoid (enteric) fever caused by Salmonella Typhi and Salmonella Paratyphi A remains a major public health problem in many parts of Asia and Africa. Currently over a third of isolates in many endemic areas are MDR, and diminished susceptibility or resistance to fluoroquinolones, the drugs of choice for MDR cases over the last decade is an increasing problem. The situation is particularly worrying in resource-limited settings where the few remaining effective antimicrobials are either unavailable or altogether too expensive to be afforded by either the general public or by public health services. Although the prudent use of effective antimicrobials, improved hygiene and sanitation and the discovery of new antimicrobial agents may offer hope for the management of invasive salmonella infections, it is essential to consider other interventions including the wider use of WHO recommended typhoid vaccines and the acceleration of trials for novel iNTS vaccines. The main objective of this review is to describe existing data on the prevalence and epidemiology of antimicrobial resistant invasive Salmonella infections and how this affects the management of these infections, especially in endemic developing countries.